Planning and Delivery of Health Services - An Article Review on Urban Aboriginal Mobility in Canada: Examining the Association With Healthcare Utilization - Dhawan, Ankit (Université d'Ottawa | University of Ottawa, 2016)
An article from Social Science and Medicine, written by Snyder and Wilson (2012), examined the use of healthcare services by urban Aboriginal populations in Canada. Using the Behavioural Model of Health Services Use (BMHSU), predisposing, enabling, and need factors were organized and used for data analysis. Specifically, a comparison was made between conventional (physicians and nurses) and traditional (traditional healers) health service utilization in Toronto and Winnipeg. In addition to the geographical and educational factors, the results of the research recognized mobility as a significant predisposing complement to healthcare utilization.
Keywords: mobility; urban; Aboriginal health; healthcare utilization; Canada